Pengaruh Pendidikan Karakter Anti-Bullying Terhadap Kesehatan Mental Pada Siswa Di SMP Negeri 19 Kota Bengkulu Tahun 2025 - Desmi Desmi; Yance Hidayat; Erlina Panca Putri (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Bullying in schools remains a serious problem that impacts students' mental health, particularly at the junior high school level. Data from the Indonesian Teachers' Union Federation shows an increase in bullying cases from 21 to 30 in 2023, with 50% occurring at the junior high school level. Furthermore, anxiety disorders are experienced by 4.1–5.3% of adolescents, and depression by 1.3–3.4%, potentially disrupting students' learning and psychological well-being. Therefore, anti-bullying character education is needed as a preventative measure to create a safe school environment and support students' mental health. This study aims to determine the effect of anti-bullying character education on student mental health at SMP Negeri 19, Bengkulu City. The method used was a pre-experimental study with a one-group pretest–posttest design. The study sample consisted of 160 students selected using stratified random sampling. The research instruments were an anti-bullying character education questionnaire and a mental health questionnaire. Data analysis was performed using univariate and bivariate methods using the Wilcoxon Signed Rank Test. The analysis showed that before the intervention, most students were in the moderate category for bullying (56.3%), and after the intervention, most were in the low category (60.6%). The mental health of students in the undisturbed category increased from 51.9% to 63.1% after the intervention. The Wilcoxon test showed a significant effect of anti-bullying character education on student mental health (p < 0.05). The researchers recommend that schools implement anti-bullying character education sustainably, including bullying prevention efforts, and improve student mental health.